Zinc air battery air electrode catalyst and preparation method and application thereof

By using the carbon material prepared by pyrolysis of sp3-rich C and N-enriched melamine formaldehyde resin microspheres as catalysts in zinc air batteries, the problem of insufficient catalytic performance of zinc air batteries is solved, and efficient oxygen reduction reaction and good battery performance are achieved.

CN119812360APending Publication Date: 2025-04-11HENAN FLUORINE BASED NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510004841.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The catalytic performance of existing zinc air batteries needs to be improved, resulting in insufficient power density, specific capacity and cycle stability.

Method used

The pyrolysis of melamine formaldehyde resin microspheres enriched with sp3 hybrid C and N enriched was prepared under urea activation, and carbon materials with rich sp3 defects and optimized nitrogen doping configuration were prepared as zinc air battery air electrode catalyst.

Benefits of technology

The catalyst exhibits efficient oxygen reduction reaction (ORR) activity, with half-wave potential as high as 0.8780V and a taffel slope as low as 72.45 mV dec-1, significantly improving the power density and specific capacity of the zinc air battery and showing good cycling stability in continuous charge and discharge tests.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812360A_ABST
    Figure CN119812360A_ABST
Patent Text Reader

Abstract

The invention relates to a zinc-air battery air electrode catalyst and a preparation method and application thereof, and belongs to the technical field of catalysis. The preparation method of the air electrode catalyst for the zinc-air battery comprises the following steps: mixing melamine formaldehyde resin with urea, and then carrying out heating treatment at 900-1000 DEG C; the mass ratio of the melamine formaldehyde resin to the urea is 1: (2-4). The obtained catalyst has a hierarchical porous structure and efficient ORR activity; when the catalyst is applied to a zinc air battery, relatively high power density and specific capacity are shown, and the cycling stability is also remarkably improved compared with that of a 20% Pt / C catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an air electrode catalyst for a zinc-air battery and a preparation method and application thereof, belonging to the technical field of catalysis. Background Art

[0002] Fuel cells, as a new energy material, have the advantages of high energy density, efficient energy conversion, and zero emissions, and have become an important direction for future energy development. Zinc-air batteries, as a special type of fuel cell, use metal zinc as the active substance for the electrochemical reaction at the negative electrode and oxygen in the air as the active substance for the electrochemical reaction at the positive electrode. They have the advantages of high energy density, abundant resources, and green and pollution-free reactive substances, and have attracted close attention from researchers.

[0003] The oxygen reduction reaction (ORR) involved in the discharge process is a key electrochemical process in rechargeable zinc-air batteries. Since ORR involves a slow multi-electron transfer reaction kinetic process, it is necessary to develop stable and efficient oxygen reduction reaction electrocatalysts for use in rechargeable zinc-air batteries. Currently, platinum-based materials are usually selected as ORR catalysts, but the ORR catalytic activity of catalysts prepared by platinum-based materials is not high, and the cost is high and the stability is poor, which greatly limits its application in rechargeable zinc-air batteries. Summary of the invention

[0004] The first object of the present invention is to provide a method for preparing a zinc-air battery air electrode catalyst, so as to solve the problem that the catalytic performance of the existing zinc-air battery air electrode needs to be improved.

[0005] The second object of the present invention is to provide an air electrode catalyst for a zinc-air battery prepared by the above preparation method.

[0006] The third object of the present invention is to provide the application of the above zinc-air battery air electrode catalyst in zinc-air batteries to solve the problem that the battery performance such as power density, specific capacity and cycle stability of existing zinc-air batteries need to be improved.

[0007] To achieve the above first purpose, the technical solution adopted by the present invention is: A method for preparing an air electrode catalyst for a zinc-air battery comprises the following steps: mixing melamine formaldehyde resin with urea, and then heating at 900-1000° C.; the mass ratio of the melamine formaldehyde resin to urea is 1:(2-4).

[0008] This invention is a pioneering invention, mainly using sp 3 Hybrid C- and N-enriched melamine formaldehyde resin microspheres were pyrolyzed and activated with urea to derive Zn-air battery air electrode catalysts with abundant sp 3Defects and optimized nitrogen doping configuration, compared with 20% Pt / C catalyst, the prepared zinc-air battery air electrode catalyst has high yield and stable quality in the preparation process, with hierarchical porous structure and uniform distribution of C, N and O elements. Based on the above special structure, the zinc-air battery air electrode catalyst exhibits type I and type IV mixed N2 adsorption and desorption isotherms, and the BET specific surface area is 789m 2 g -1 The average pore size is about 3.38 nm, which is beneficial to the improvement of the ORR activity of the air electrode catalyst of zinc-air batteries.

[0009] The hierarchical porous structure exposes more active sites to enhance electron transfer and mass transfer. ORR catalytic experiments show that the half-wave potential of the catalyst is as high as 0.8780 V and the Tafel slope is as low as 72.45 mV dec. -1 , showing efficient ORR activity.

[0010] Preferably, the heating treatment time is 1 to 3 h.

[0011] Preferably, the melamine formaldehyde resin is obtained by prepolymerizing formaldehyde and melamine in water and then adding acid to continue the reaction.

[0012] Preferably, the amount of melamine used is 2-3 g for every 9-10 g of 37-40 wt % formaldehyde solution, the prepolymerization is carried out at 80-85° C. for 20-25 min, and the reaction after adding the acid is carried out at 80-85° C. for 40-50 min.

[0013] Further preferably, the acid is added in the form of formic acid solution, and the amount of water corresponding to every 9-10 g of 37-40 wt% formaldehyde solution is 200-250 mL, and the amount of formic acid solution corresponding to the amount is 0.3-0.5 mL; the concentration of the formic acid solution is 22-24 mol / L.

[0014] Preferably, the mass ratio of the melamine formaldehyde resin to urea is 1:3-3.2, the temperature of the heating treatment is 950-960° C., and the time is 2-2.5 h.

[0015] To achieve the above second purpose, the technical solution adopted by the present invention is: An air electrode catalyst for a zinc-air battery prepared by the preparation method.

[0016] The zinc-air battery air electrode catalyst has uniform distribution of C, N and O elements, a hierarchical porous structure and efficient ORR activity, and has a high yield and stable quality, and can be applied to zinc-air batteries.

[0017] To achieve the third purpose, the technical solution adopted by the present invention is: Application of the above zinc-air battery air electrode catalyst in zinc-air batteries.

[0018] By constructing a zinc-air battery with carbon paper coated with zinc-air battery air electrode catalyst as air cathode, zinc as anode, and alkaline electrolyte, it is found that the prepared zinc-air battery has a higher power density (174.1 mW cm) than the zinc-air battery prepared with 20% Pt / C catalyst. -2 ) and specific capacity (797mA hg· Zn -1 ), showing good battery performance. The cycle performance test results show that the charge and discharge voltage has almost no change in the continuous charge and discharge test of at least 250 hours (1500 cycles), showing good cycle stability.

[0019] Preferably, the air cathode of the zinc-air battery comprises the air electrode catalyst and RuO2, and the mass ratio of the air electrode catalyst to RuO2 is (1-1.2): (1-1.2). BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The scanning electron microscope image, transmission electron microscope image, high-angle annular dark field image and energy dispersive X-ray spectrum image of the air electrode catalyst of the zinc-air battery in Example 1 of the present invention are shown; Figure 1 a in the figure is a 10 μm structure diagram of the air electrode catalyst of the zinc-air battery observed under a scanning electron microscope; Figure 1 b is a 5 μm structure diagram of the air electrode catalyst of the zinc-air battery observed under a scanning electron microscope; Figure 1 c is a 2 μm structure diagram of the air electrode catalyst of the zinc-air battery observed under a scanning electron microscope; Figure 1 d in the figure is the 20 nm structure of the air electrode catalyst of the zinc-air battery observed under a transmission electron microscope; Figure 1 e in the figure is a 50 nm structure diagram of the air electrode catalyst of the zinc-air battery observed under a transmission electron microscope; Figure 1 f in the figure is a high-angle annular dark field image and energy dispersive X-ray spectrum image (500 nm structure image) of the air electrode catalyst of the zinc-air battery; Figure 2 This is a diagram showing a physical adsorption test of the air electrode catalyst of the zinc-air battery in Example 1 of the present invention; Figure 2 a in the figure is the N2 adsorption-desorption isotherm of the air electrode catalyst of the zinc-air battery; Figure 2 b is the pore size distribution diagram of the air electrode catalyst of the zinc-air battery; Figure 3The linear sweep voltammetry (LSV) scanning diagram, Tafel slope diagram and LSV curves at different rotation speeds of the air electrode catalyst of the zinc-air battery in Example 1 of the present invention (the inset is the KL equation curve); Figure 3 a in the figure is the linear sweep voltammetry (LSV) scan diagram; Figure 3 b in the figure is the Tafel slope plot; Figure 3 c in the figure is the LSV curve at different speeds (the inset is the KL equation curve); Figure 4 The linear sweep voltammetry (LSV) scanning diagrams of the air electrode catalysts of the zinc-air battery according to different embodiments of the present invention are shown; Figure 5 This is a performance comparison chart of the zinc-air battery air electrode catalyst based on Example 1 of the present invention and the zinc-air battery coated with 20% Pt / C catalyst; wherein Figure 5 a in it is the discharge polarization curve and power density curve; Figure 5 b in the figure is the open voltage circuit diagram; Figure 5 c in the figure is the rate performance curve at different current densities; Figure 5 d in the figure is the specific capacity diagram of zinc-air battery; Figure 5 The e in FIG. is the charge and discharge cycle performance diagram of the zinc-air battery. DETAILED DESCRIPTION

[0021] The technical concept of the present invention is to use sp 3 Hybrid C and N-enriched melamine formaldehyde resin (MF) microspheres were pyrolyzed to prepare highly active carbon materials under urea activation. The obtained carbon materials have rich sp 3 The defects and optimized nitrogen-doped configuration, as well as the hierarchical porous structure, show excellent ORR activity. The power density, specific capacity and cycle stability of the zinc-air battery based on this catalyst are all good.

[0022] The implementation process of the present invention is described in detail below in conjunction with specific embodiments. Unless otherwise specified, the products used in the following embodiments are all commercially available conventional products. The synthesis method of melamine formaldehyde resin is as follows: (1) Add 9.8 g of 37 wt% formaldehyde solution and 200 mL of water into a 500 mL three-necked flask, stir with a magnetic stirrer, and heat to 80 °C in a water bath; (2) Add 2.5 g of melamine to the above solution and react at 80°C for 20 min to generate a prepolymer; (3) Add 0.3 ml of formic acid solution (concentration: 23 mol / L) to the solution, continue stirring at 80°C for 40 min, and then stop the reaction; (4) The obtained product was centrifugally washed twice with water and ethanol (10000 rpm, 15 min), respectively, and dried at 60 °C to obtain white powdery melamine formaldehyde resin microspheres.

[0023] 1. Specific embodiments of a zinc-air battery air electrode catalyst and a preparation method thereof according to the present invention Example 1 The preparation method of the zinc-air battery air electrode catalyst of this embodiment adopts the following steps: melamine formaldehyde resin microspheres and urea are fully mixed in a mass ratio of 1:3, and the mixture is placed in a tube furnace; heating to 950°C at a heating rate of 5°C / min and maintaining for 2 h, and naturally cooling to room temperature to obtain a zinc-air battery air electrode catalyst (denoted as MFC).

[0024] Example 2 The preparation method of the zinc-air battery air electrode catalyst of this embodiment is different from that of Example 1 in that: melamine formaldehyde resin microspheres and urea are fully mixed in a ratio of 1:2, and the mixture is placed in a tubular furnace; the mixture is heated to 950°C at a heating rate of 5°C / min and maintained for 2 h, and the obtained zinc-air battery air electrode catalyst is MF+urea-950-2 (1:2).

[0025] Example 3 The preparation method of the zinc-air battery air electrode catalyst of this embodiment is different from that of Example 1 in that: melamine formaldehyde resin microspheres and urea are fully mixed in a ratio of 1:4, and the mixture is placed in a tubular furnace; the mixture is heated to 950°C at a heating rate of 5°C / min and maintained for 2 h to obtain the zinc-air battery air electrode catalyst MF+urea-950-2 (1:4).

[0026] Example 4 The preparation method of the zinc-air battery air electrode catalyst of this embodiment is different from that of Example 1 in that: melamine formaldehyde resin microspheres and urea are fully mixed in a ratio of 1:3, and the mixture is placed in a tubular furnace; the mixture is heated to 900°C at a heating rate of 5°C / min and maintained for 2 h to obtain the zinc-air battery air electrode catalyst MF+urea-900-2 (1:3).

[0027] Example 5 The preparation method of the zinc-air battery air electrode catalyst of this embodiment is different from that of Example 1 in that: melamine formaldehyde resin microspheres and urea are fully mixed in a ratio of 1:3, and the mixture is placed in a tubular furnace; the mixture is heated to 1000°C at a heating rate of 5°C / min and maintained for 2 h to obtain the zinc-air battery air electrode catalyst MF+urea-1000-2 (1:3).

[0028] Example 6 The preparation method of the zinc-air battery air electrode catalyst of this embodiment is different from that of Example 1 in that: melamine formaldehyde resin microspheres and urea are fully mixed in a ratio of 1:3, and the mixture is placed in a tubular furnace; the mixture is heated to 950°C at a heating rate of 5°C / min and maintained for 1 h to obtain the zinc-air battery air electrode catalyst MF+urea-950-1 (1:3).

[0029] Example 7 The preparation method of the zinc-air battery air electrode catalyst of this embodiment is different from that of Example 1 in that: melamine formaldehyde resin microspheres and urea are fully mixed in a ratio of 1:3, and the mixture is placed in a tubular furnace; the mixture is heated to 950°C at a heating rate of 5°C / min and maintained for 3 h to obtain the zinc-air battery air electrode catalyst MF+urea-950-3 (1:3).

[0030] 2. Specific examples of the application of the air electrode catalyst of the zinc-air battery of the present invention in the zinc-air battery Example 8 This embodiment is the application of the air electrode catalyst of the zinc-air battery in the zinc-air battery. The specific operation is as follows: the air electrode catalyst of the zinc-air battery of Example 1 is mixed with RuO2 (mass ratio = 1:1) as a cathode catalyst, and coated (the loading amount of the mixed air electrode catalyst of the zinc-air battery of Example 1 and RuO2 is 1 mg·cm -2 ) on carbon paper as the air cathode, a polished zinc plate (thickness: 0.5 mm) as the anode, and 6 M KOH (containing 0.2 M zinc acetate) solution as the alkaline electrolyte to construct a Zn-air battery.

[0031] Specifically, the carbon paper was cut into 2*2 cm squares, and 10 μL of the catalyst solution was applied to the middle of the carbon paper each time with a pipette. This was repeated 20 times, with a total of 200 μL applied. The loading amount was 1 mg cm -2 , forming an area of ​​1cm 2 Catalyst solution preparation process: 2.5 mg of catalyst and 2.5 mg of RuO2 were dispersed in 1 ml of ethanol, and then 20 μL of 5wt% Nafion (dispersant, commercially available) was added and ultrasonicated for 30 min to prepare a 5 mg / ml solution.

[0032] 3. Comparison Comparative Example 1 The air electrode catalyst of the zinc-air battery in this comparative example is obtained by directly pyrolyzing melamine formaldehyde resin microspheres at 950°C for 2h without mixing with urea (other conditions are the same as those in Example 1), and the obtained substance is recorded as MFC‵.

[0033] IV. Experimental Examples Experimental Example 1 In this experimental example, the zinc-air battery air electrode catalyst MFC obtained in Example 1 was observed using a scanning electron microscope (SEM), a transmission electron microscope (TEM), a high-angle annular dark field (HAADF) and an energy dispersive X-ray (EDS), and a physical adsorption test (BET) was performed. The results are as follows: Through SEM observation ( Figure 1 a~c in the figure), it was found that the zinc-air battery air electrode catalyst MFC showed the characteristics of porous carbon covered by carbon sheets; it was placed under TEM for observation ( Figure 1 d~e), revealing more details, it can be seen that the carbon sheets are mixed with layered porous amorphous carbon, which is consistent with the images observed under SEM; HAADF images and EDS spectral mapping show that the C, N and O elements are evenly distributed in the air electrode catalyst of the zinc-air battery ( Figure 1 f).

[0034] BET test found that the zinc-air battery air electrode catalyst MFC showed a type I and IV mixed N2 adsorption-desorption isotherm, which showed a sharp increase trend at a lower relative pressure (P / P0<0.1) and a hysteresis phenomenon at a high relative pressure (P / P0>0.6). Figure 2 The BET specific surface area of ​​the air electrode catalyst of the zinc-air battery is 789 m 2 g -1 , the average pore size is about 3.38 nm ( Figure 2 b), which indicates that the zinc-air battery air electrode catalyst MFC has a hierarchical porous structure, which is beneficial to the improvement of the ORR activity of the zinc-air battery air electrode catalyst.

[0035] Experimental Example 2 Test of ORR activity of air electrode catalyst in zinc-air battery This experimental example tests the ORR activity of the zinc-air battery air electrode catalyst and the 20% Pt / C catalyst obtained in Examples 1 to 7, and the specific description is as follows: The obtained zinc-air battery air electrode catalyst and 20% Pt / C catalyst were tested under CHI760E electrochemical workstation respectively. Platinum wire was used as counter electrode, Ag / AgCl as reference electrode and catalyst-coated glassy carbon (diameter 5.0 mm) electrode as working electrode. The working electrode preparation process is as follows: 2 mg of catalyst was dispersed in 1 ml of a mixed solvent of ethanol and water (the volume ratio of ethanol to water was 9:1), and then 10 μL of 5wt% Nafion (dispersant, commercially available) was added, and ultrasonicated for 30 min to make it evenly dispersed, and 25 μL of the dispersed liquid was dropped on the glassy carbon electrode and dried at room temperature. In O2 - / N2 saturated 0.1 M KOH solution (preparation method: use a 1L volumetric flask to prepare the solution, first weigh 5.6 g of KOH solid in a small beaker, dissolve it with a small amount of pure water, and stir it with a glass rod. After the solution cools to room temperature, transfer the dissolved solution to the volumetric flask, wash the small beaker and glass rod with pure water 2-3 times, transfer the washing solution to the volumetric flask, and adjust the volume to 1L) for cyclic voltammetry (CV) at a scan rate of 50 mV·s -1 ; In an O2-saturated 0.1 M KOH solution (preparation method is the same as O2 - Linear sweep voltammetry (LSV) was performed at different speeds (400-2025 rpm) in 0.1 M KOH solution saturated with N2 at a scan rate of 5 mV·s -1 In the present invention, all potentials are converted to standard hydrogen potential RHE.

[0036] The number of electron transfers (n) and the kinetic current density (J k ) can be calculated using the Koutecký-Levich (KL) equation: 1 / J = 1 / J k + 1 / (Bω 1 / 2 ) (1) Where J is the current density, J k is the dynamic current density, and ω is the electrode rotation rate. B is determined by the Levich slope: B = 0.2 nF C0D0 2 / 3 v -1 / 6 (2) where F is the Faraday constant (F = 96485 C mol -1 ). C0 is the concentration of O2 in 0.1 M KOH solution (C0 = 1.2 × 106 mol cm 3 ). D0 is the diffusion coefficient of O2 in the electrolyte solution (D0 = 1.9×10 -5 cm 2 s -1 ), v is the kinematic viscosity of the electrolyte (v = 0.01 cm 2 s -1 ). When the speed is expressed in rpm, a constant of 0.2 is used.

[0037] The reference formula for electron transfer number and hydrogen peroxide yield (H2O2%) is as follows: (3) (4) I d is the disk current; I ris the ring current; N is the collection coefficient of the Pt ring electrode, which is 0.37.

[0038] Linear sweep voltammetry (LSV) scanning diagram of the zinc-air battery air electrode catalysts MFC, MFC‵, and 20% Pt / C catalyst obtained in Example 1 ( Figure 3 (a~b) in the figure shows that the half-wave potential of the zinc-air battery air electrode catalyst MFC is 0.8780 V, which is significantly higher than that of the 20% Pt / C catalyst; the Tafel slope is 72.45 mV dec -1 , which is significantly lower than that of 20% Pt / C catalyst. This is due to the hierarchical porous structure of the zinc-air battery air electrode catalyst, which exposes more active sites to enhance electron transfer and mass transfer, making the zinc-air battery air electrode catalyst have efficient ORR activity.

[0039] By fitting the LSV curves at different rotation speeds, a series of parallel KL curves were obtained. The electron transfer number n was calculated using the Kouteky-Levich (KL) equation to be approximately 4.00 (Figure 3 c), confirming that the catalyst follows an ideal four-electron reaction path during the reaction. The transfer pathway and hydrogen peroxide yield of the catalyst were tested by rotating ring disk electrode (RRDE) in the potential range of 0.50 V to 0.90 V. The measured electron transfer number was 3.95, and the H2O2 yield was less than 14.17%, further confirming that 4e - dominated the ORR process ( Figure 3 c).

[0040] Linear sweep voltammetry (LSV) scanning diagram of the zinc-air battery air electrode catalyst obtained in Example 1 and the zinc-air battery air electrode catalyst obtained in Examples 2 to 7 ( Figure 4 ) shows that the half-wave potential of the zinc-air battery air electrode catalyst obtained in Example 1 is 0.8780 V, which is higher than that of the zinc-air battery air electrode catalysts obtained in Examples 2 to 7; the Tafel slope is 72.45 mV dec -1 , which is lower than the zinc-air battery air electrode catalysts obtained in Examples 2 to 7, indicating that the zinc-air battery air electrode catalyst obtained in Example 1 exhibits better ORR activity.

[0041] Experimental Example 3 Battery Performance Test of Zinc-Air Battery In this experimental example, the catalyst MFC and 20% Pt / C catalyst of Example 1 were used to prepare a zinc-air battery according to the method of Example 8, and the battery performance was tested. All tests were performed at room temperature.

[0042] According to the discharge polarization curve and power density curve ( Figure 5a in Figure 1; test conditions: starting potential 1.444 v, ending potential -1 v, scan rate 0.01 v / s), it was found that the power density of the zinc-air battery with the zinc-air battery air electrode catalyst as the air cathode was 174.1 mW cm -2 , which is much higher than the power density of zinc-air battery with 20% Pt / C catalyst as air cathode (85.3 mW cm -2 The open circuit voltage of the zinc-air battery made based on the zinc-air battery air electrode catalyst is 1.48 V, which is slightly lower than the open circuit voltage of the zinc-air battery made based on the 20% Pt / C catalyst (1.50 V, Figure 5 b in the figure; test conditions: high potential: 2 V, low potential: 0 V, running time: 600 s; “Two MFC in series” refers to the open circuit voltage of two zinc-air batteries assembled with MFC catalysts in series; “Two Pt / C in series” refers to the open circuit voltage of two zinc-air batteries assembled with Pt / C catalysts in series).

[0043] By studying the discharge curves of zinc-air battery air electrode catalyst MFC and 20% Pt / C catalyst at different current densities ( Figure 5 c), it can be seen that the potential of the zinc-air battery air electrode catalyst does not drop significantly compared with the 20% Pt / C catalyst; at 5 mA·cm -2 At a current density of , the discharge capacity curve is obtained based on the mass of zinc consumed ( Figure 5 (d) shows that the specific capacity of the zinc-air battery made based on the air electrode catalyst of the zinc-air battery is as high as 797 mA h g· Zn -1 , which is much higher than the specific capacity of zinc-air batteries made with 20% Pt / C catalyst (732 mA h g· Zn -1 ).

[0044] The Zn-air battery was cycled using a 5 min charge and 5 min discharge periodic galvanostatic pulse with a current density of j = 5 mA cm -2 The test results show that ( Figure 5 e), the zinc-air battery made of a mixture of zinc-air battery air electrode catalyst and RuO2 has almost no change in charge and discharge voltage during a continuous charge and discharge test of at least 250 hours (1500 cycles), while the zinc-air battery made of a mixture of 20% Pt / C and RuO2 has a large change in charge and discharge voltage during a shorter cycle period of about 80 hours, indicating that the zinc-air battery made of a mixture of zinc-air battery air electrode catalyst and RuO2 has good cycle stability.

[0045] The cell performance test was conducted on the catalysts of Examples 2 to 6, and their performance was comparable to or slightly inferior to that of the 20% Pt / C catalyst.

[0046] The above specific embodiments further illustrate the purpose, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing an air electrode catalyst for a zinc-air battery, characterized in that: The following steps are involved: The melamine formaldehyde resin is mixed with urea, and then heated at 900-1000° C. The mass ratio of the melamine formaldehyde resin to the urea is 1:(2-4).

2. The method for preparing an air electrode catalyst for a zinc-air battery according to claim 1, wherein: The heating treatment time is 1 to 3 h.

3. The method for preparing the air electrode catalyst for zinc-air battery according to claim 1, characterized in that: The melamine formaldehyde resin is obtained by prepolymerizing formaldehyde and melamine in water and then adding acid to continue the reaction.

4. The method for preparing the air electrode catalyst for a zinc-air battery according to claim 3, characterized in that: The amount of melamine used for every 9-10g of 37-40 wt% formaldehyde solution is 2-3g. The prepolymerization is carried out at 80-85°C for 20-25min. The reaction after adding the acid is carried out at 80-85°C for 40-50min.

5. The method for preparing the air electrode catalyst for zinc-air battery according to claim 4, characterized in that: The acid is added in the form of formic acid solution. For every 9-10 g of 37-40 wt% formaldehyde solution, the corresponding amount of water is 200-250 mL, and the corresponding amount of formic acid solution is 0.3-0.5 mL. The concentration of the formic acid solution is 22-24 mol / L.

6. The method for preparing an air electrode catalyst for a zinc-air battery according to claim 1, characterized in that: The mass ratio of the melamine formaldehyde resin to urea is 1:3-3.2, the temperature of the heating treatment is 950-960° C., and the time is 2-2.5 hours.

7. An air electrode catalyst for a zinc-air battery prepared by the preparation method according to any one of claims 1 to 6.

8. Use of the zinc-air battery air electrode catalyst as claimed in claim 7 in a zinc-air battery.

9. Use of the zinc-air battery air electrode catalyst as claimed in claim 8 in a zinc-air battery, characterized in that: The air cathode of the zinc-air battery comprises the air electrode catalyst and RuO2, and the mass ratio of the air electrode catalyst to RuO2 is (1-1.2): (1-1.2).